Multi-dimensional dynamic fluorescence readout from laser engineered In2O3 nanowire micropatterns. Issue 16 (19th April 2023) - Poh, Eng Tuan; Tan, Yung Zhen; Neo, Justin Boon Shuan; Ong, Chee How; Saroni, Azianty; Zhang, Zheng; Li, Jianhui; Goh, Boon Tong; Sow, Chorng Haur
Abstract : A laser-irradiated array of In2 O3 nanowires presents yellow and blue fluorescence states that can be dynamically altered under UV light for anti-counterfeiting features based upon microscale patterning, color evolution and time-domain encoding. Abstract : Laser-induced microscale reactions are an excellent means to obtain controllable, small-scale insights into nanomaterial properties. Importantly, the opportunity for a comprehensive understanding of the material's optical origins allows for refined engineering of material luminescence. Modifying an array of standing indium oxide (In2 O3 ) nanowires with a focused laser beam, we report newfound yellow and blue fluorescence emanating from the sample. Evaluated through a broad range of laser conditions, the laser-induced yellow component was found to relate to oxygen inclusions, while the blue fluorescence overlayer originated from oxygen physisorption upon prolonged storage. Capitalizing on the versatility of the blue emission component under UV modulation, we demonstrate micropatterns with multiple layers of differentiated optical encryption features. The enhanced anti-counterfeiting capability allows improved complexity in an authentication process, involving the convergence of microscale patterning, dynamic color evolution and time-domain encoding as multilevel checkpoints in the verification process.